(untitled) (Ustozlar uchun, 2026)
Reading skills are fundamental for language acquisition, academic success, and lifelong learning. They enable learners to comprehend, analyze, and interpret written texts, facilitating knowledge acquisition across disciplines. This article explores the components, strategies, and instructional methods for developing reading skills in English, highlighting their significance in improving comprehension, critical thinking, and overall language proficiency.